2021
DOI: 10.1111/1365-2435.13945
|View full text |Cite
|
Sign up to set email alerts
|

Opportunities, challenges and pitfalls in characterizing plant water‐use strategies

Abstract: 1. Classifying the diverse ways that plants respond to hydrologic stress into generalizable 'water-use strategies' has long been an eco-physiological research goal.While many schemes for describing water-use strategies have proven to be quite useful, they are also associated with uncertainties regarding their theoretical basis and their connection to plant carbon and water relations. In this review, we discuss the factors that shape plant water stress responses and assess the approaches used to classify a plan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 52 publications
(46 citation statements)
references
References 109 publications
(115 reference statements)
1
42
0
Order By: Relevance
“…Alternately, as σ increases, the plant moves toward anisohydric behavior, where it allows ψ x to decline (by regulating stomata less) with ψ s in order to prolong transpiration at the risk of hydraulic damage. Although there are confounding factors to the isohydricity concept (Feng et al., 2019; Novick et al., 2019), σ nevertheless provides useful insight into the inter‐ and intraspecific variability of plant water use strategies (Kannenberg et al., 2021). We fit the isohydricity index, σ , to each site and performed a species‐level comparison using a single factor ANOVA and pairwise t ‐tests using Tukey's HSD test to determine if σ values for each species differed and by how much.…”
Section: Methodsmentioning
confidence: 99%
“…Alternately, as σ increases, the plant moves toward anisohydric behavior, where it allows ψ x to decline (by regulating stomata less) with ψ s in order to prolong transpiration at the risk of hydraulic damage. Although there are confounding factors to the isohydricity concept (Feng et al., 2019; Novick et al., 2019), σ nevertheless provides useful insight into the inter‐ and intraspecific variability of plant water use strategies (Kannenberg et al., 2021). We fit the isohydricity index, σ , to each site and performed a species‐level comparison using a single factor ANOVA and pairwise t ‐tests using Tukey's HSD test to determine if σ values for each species differed and by how much.…”
Section: Methodsmentioning
confidence: 99%
“…The lack of significant correlation in between RWC and δ 2 H early July is potentially Differentials between the volumes of root water uptake and transpiration drive changes in tissue water content (Chitra-Tarak et al, 2018;Dralle et al, 2020;Nehemy et al, 2021). Reductions in tree stored water across the growing season have been described as the temporal integration of soil water stress occurring over weeks to months (Kannenberg et al, 2022). In contrast with this concept, we observed that RWC in higher elevation hemlock (experiencing substantially lower soil water availability) tended to have higher RWC from March through May and similar RWC to lower elevation trees from June through September (Fig.…”
Section: Water Use Strategy Based On Coordination Of Rooting Uptake D...mentioning
confidence: 99%
“…How plant water use strategies are defined is an evolving concept that connects the dimensions of stomatal regulation in response to vapor pressure deficits, xylem resistance to embolism, trunk water storage, root access to subsurface water sources, foliar water uptake, and carbon investments during periods of stress (Carminati & Javaux, 2020;Kannenberg et al, 2022). Investment in deeper or denser rooting systems can provide trees access to more temporally stable water sources (Chitra-Tarak et al, 2018;Fan et al, 2017;Knighton et al, 2021;Mackay et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, leaf area changes via leaf abscission and regrowth (Dallstream & Piper, 2021; Filewod & Thomas, 2014) can change plant demand for water. Indeed, seasonal shifts in plant allometry can significantly impact hydraulic regulation, sometimes exceeding the influence of environmental variables (Kannenberg et al, 2021; Novick et al, 2019). Although allometric methods can be destructive and/or labour‐intensive, repeated measurements of plant allometry within a season can shed additional light on variable hydraulic regulation.…”
Section: Discussionmentioning
confidence: 99%
“…We also found species‐dependent changes in standardized stomatal sensitivity at the subannual scale, consistent with the findings of Wu et al (2021) at the inter‐annual scale. Future studies that incorporate multiple metrics of hydraulic regulation (reviewed in Feng et al, 2019) have the potential to reveal coordination, particularly between response‐ and trait‐based metrics (Kannenberg et al, 2021).…”
Section: Discussionmentioning
confidence: 99%